Images in textbooks: Analyzes articles in science teaching journals - Geglio, Paulo César; Soares , Daniela Gomes (Seven Editora, 2023)
With the evolution of technologies, the image, which invades the contemporary world and proliferates, becomes a powerful and broad tool that can be used as an object of knowledge construction. In the present work, we seek to make an analysis of how articles published in journals of Science Education have approached the use of the photographic image in science and biology textbooks. Our research is a bibliographic review of the articles available in four national journals in the last 10 years (2010 – 2020). The consultation was carried out directly on the websites of the journals. We searched for keywords such as "Textbook", "Science/Biology". Subsequently, the abstracts of the articles were read in order to know which of them approached the image, especially the photographic image in their studies. We understand that in the analyzed articles, the photographic image is still little researched within the Science Teaching. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-030